ENTERTAINMENT-BASED CONTENT PRODUCTION STRATEGIES FOR BUILDING AUDIENCE ENGAGEMENT ON INSTAGRAM REELS AND TIKTOK: A CASE STUDY OF WULING MOTORS INDONESIA - Medo Maulianza; Nur Asni Gani; Farrel Nayesa Syahrial (Taksasila Edukasi Insani, 2026)
This study aims to examine how an otomotive company develops and implements entertainment-based content strategies on Instagram Reels and TikTok to build audience engagement. A qualitative case study approach was employed, with data collected through semi-structured interviews, content observation, and document analysis. The data were analyzed using thematic analysis to identify strategic communication practices across the stages of pre-production, production, and post-production. The findings reveal that audience engagement is generated through an integrated communication process involving audience insight, trend analysis, storytelling, creative execution, platform adaptation, and continuous performance evaluation. Rather than functioning as isolated production activities, these stages form a continuous strategic communication cycle in which audience feedback informs subsequent content development. The study proposes the Strategic Entertainment Content Production Framework (SECPF), highlighting audience engagement as both the outcome and feedback mechanism of strategic digital communication. These findings contribute to the literature on strategic digital communication and provide practical insights for organizations seeking to optimize entertainment-based communication on short-form video platforms.Keywords: strategic digital communication; entertainment-based content; content production; audience engagement; Instagram Reels; TikTok.